Selective Solid-Phase Extraction of Zn(II) by An Ion-Imprinted Polymer from Environmental and Biological Samples - Xi, Mangsong; Huang, Zhangjie; Li, Pengwei (Asian Journal of Chemistry, 2012)
A new ion-imprinted polymer material was synthesized by copolymerization of acrylamine as monomer, pentacrythritol triacrylate as crosslinking agent and 2,2'-azobisisobutyronitrile as initiator in the presence of zinc(II)-2-ethylhexyl benzimidazolyl sulfide complex. The ionimprinted polymer was used as sorbent in a solid-phase extraction column. The effects of sampling volume, elution conditions, sample pH and sample flow rate on the extraction of zinc ions from environmental and biological samples were studied. The maximum adsorption capacity and the relative selectivity coefficients of imprinted polymer for Zn(II)/Co(II), Zn(II)/Cu(II) and Zn(II)/ Ni(II) were calculated. Compared with non-imprinted polymer particles, the ion-imprinted polymer had higher selectivity for Zn(II). The detection limit for 100 mL of sample was 0.5 μg L-1 using flame atomic absorption spectrometry. The analytical results for the certified reference samples (GBW07603) were in a good agreement with the certified value. The relative standard deviation for eleven replicate sample of 8 μg L-1 level is 3.1 %. The developed method was successfully applied to the determination of trace zinc in environmental and biological samples with satisfactory results.